Global Research Trends in CBT for Children with ASD: A Bibliometric Analysis of Disparities Between Developed and Developing Countries - Vernando Yanry Lameky; La Saudi; Anita Apriliawati; Titin Sutini; Nurul Anjarwati; Mei Lestari Ika Widyyati (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
ntroduction: Autism spectrum disorder (ASD) is a neurodevelopmental condition with an increasing global prevalence that demands effective intervention strategies. Cognitive behavioral therapy (CBT) is a well-researched approach for treating various co-occurring disorders in children with ASD. However, despite the growing volume of research, there remains a lack of comprehensive bibliometric analysis that maps global trends, thematic focus, and collaboration patterns in CBT-related ASD studies, highlighting a critical gap that this study seeks to address. Methods: This study used a bibliometric approach to analyze global research trends in CBT for treating children with ASD. It analyzed 148 articles published between 2007 and 2025. Data were collected from the Scopus database and analyzed using VOSviewer, Harzing's Publish or Perish, and Microsoft Excel. This bibliometric analysis provides a novel perspective by quantitatively mapping the evolution of research, identifying underexplored themes, and revealing disparities in scientific contributions between developed and developing countries, an area that has received limited attention in existing CBT-ASD literature. Results: The results showed a significant upward trend in publications on CBT for ASD since 2007, peaking by 2025. The United States, the United Kingdom, Canada, and Australia dominated the geographical distribution of research, whereas developing countries had limited contributions. Collaboration patterns revealed strong connections between developed countries, with the United States as the main center. This study focused on the effectiveness of CBT in managing anxiety disorders, improving social skills, and addressing comorbidities, such as obsessive-compulsive disorder and sleep problems. However, there are research gaps in the application of CBT for severe ASD and in the involvement of developing countries. Conclusion: This study offers a novel bibliometric insight into the evolution and focus of CBT research in ASD, highlighting underexplored areas for future inquiry. Its implications can be extended to health practitioners, policymakers, educators, and researchers. Future research should explore the adaptation of CBT to various cultural contexts and ASD severity, utilizing technological advancements and multidisciplinary collaboration to provide more inclusive and accessible interventions for children with ASD worldwide.